Pengaruh Promosi dan Kualitas Pelayanan Terhadap Tingkat Kunjungan Wisata di Kota Padang - Syahril - (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2015)
This study entitled Effect of Promotion and Service Quality Level Against Travel Visits in the city of Padang. The phenomena that occur in the city of Padang about is the lack of promotion of the tourist city of Padang and the lack of quality of service, resulting in a decline in tourist visitors who come to the city Padang. Be caused this phenomenon I am interested in doing research. The variables in this study, namely the promotion, and quality of service as the independent variable (X) and Level Visits Tourism as the dependent variable (Y). The population of 100 people and the entire population sample directly sampled with a total random sampling technique or census. Data analysis technique used multiple regression analysis techniques with the formula:Y = a + b1.X1 + b2.X2 +e The results of this study are based on t test or partial test where promotion variables no significant effect on the variable level of tourist traffic in the city of Padang, because the promotion variable exists at t <t table or sig. ≥ α is 0.720> 0.05. Variable promotion has a regression coefficient of 0.050 means not contribute terhadapTingkat excursions in Padang. While the quality of service significantly influence the level of tourist traffic in the city of Padang, because it has smoothly t> t table or sig. ≥ α is 0.00 <0.05. Variable quality of service has a regression coefficient of 0.533 means that if the quality of service increases by one unit, then the rate of increase of tourist visits Junga 0.533.Keywords: promotion, quality of service and level of tourist visits